Synergistic regenerative effects of functionalized endometrial stromal cells with hyaluronic acid hydrogel in a murine model of uterine damage - Kim, Yoon Young; Park, Kyu Hyung; Kim, Yong Jin; Kim, Moon Suk; Liu, Hung Ching; Rosenwaks, Zev; Ku, Seung Yup (Acta Biomaterialia, 2019)
Clinically intractable infertility and recurrent miscarriage due to irreversible endometrial damage need to be treated with biomaterial- and cell-based therapies. Some previous studies have reported on the efficacy of a collagen scaffold and/or bone marrow-derived mesenchymal stem cells. However, the functional differentiation of grafted cells was uncertain, and the time required for regeneration was long in these studies. Here, we show the synergistic regenerative effects of hyaluronic acid (HA) hydrogel with in vitro decidualized endometrial stromal cells (EMSCs) in a murine uterine infertility (synechiae) model. Decidualized EMSCs (dEMSCs) were encapsulated with HA hydrogel, combined with three different doses of fibrinogen/thrombin (5, 50, and 500 mIU/mL). The HA/fibrin gel showed biocompatibility when mixed with dEMSCs. The addition of thrombin enhanced gel formation (5 and 50 mIU/mL) and engraftment and enabled the effective release of adhesion molecules. Within two weeks, which is a short duration, treatment with hydrogel decreased the fibrous tissue and increased the thickness of the endometrium. The regenerated endometrium demonstrated functional recovery, as evidenced by the expression and secretion of molecules essential for embryonic implantation, such as Desmin, CD44, PECAM, and IGF-1. Transferred embryos successfully implanted and the normal development of implanted embryos (n = 37) were evaluated by co-localization of distinct markers of the three germ layers (Sox2, Nestin, Brachyury, AFP, and HNF4α). Live birth of offspring was achieved in the regenerated endometrium by HA hydrogel. Therefore, HA hydrogel-mixed dEMSCs can be an innovative treatment strategy with rapid recovery of endometrial damage and may also have therapeutic potential in intractable infertility or recurrent miscarriage. Statement of Significance: Decidualized EMSCs (dEMSCs) encapsulated with HA hydrogel combined with fibrinogen/thrombin (50 mIU/mL) showed injectability and biocompatibility when mixed with dEMSCs. Hydrogel-encapsulated dEMSCs can be a useful treatment for damaged endometrium in short duration, with successful implantation and normal development in a murine model.
Keywords: Cell-be; Cell/B.E; Cell/BE; Decidualization; Endometrial regeneration; Endometrial stromal cell; Hyaluronic acid hydrogels; Murine model; Regenerative effects; Stromal cells; Animals; Disease Models, Animal; Endometrium; Extracellular Matrix; Female; Hyaluronic Acid; Hydrogels; Mice; Stromal Cells; Decidualization; Endometrial regeneration; Endometrial stromal cells; Hyaluronic acid; Hydrogel